The Impact of Work accidents on Productive efficiency in Sudan some factories: (A case study of operate in the White Nile State) - د. نضال حماد على حماد (White Nile Journal for Studies and Research, 2021)
The paper studies the impact of work accidents in Sudan in a case of some factories in the White Nile State. Aimed at clarifying their impact on the work of selected factories. The study assumed an important hypothesis that work accidents affect negatively the productive efficiency of the selected plants. Using the analytical descriptive approach the study reached a number of results, the most important of which is that work accidents reduce productivity efficiency in the factory. Absence of use of safety measures by workers increases work accidents. The study recommended for reducing work accidents by using safety means and to conduct training courses for workers, especially when providing modem machines. Keywords: work accidents, productivity efficiency, safety means.